Improvement of the Activity of a Fungal Versatile-Lipase Toward Triglycerides: An in silico Mechanistic Description - Payá-Tormo, Lucía; Rodríguez-Salarichs, Javier; Prieto, Alicia; Martínez, María Jesús; Barriuso, Jorge (Frontiers in Bioengineering and Biotechnology, 2019)
Some enzymes that belong to the Candida rugosa-like lipase family (abH03.01) combine the activities of lipases and sterol esterases. Thus, they can act on water-insoluble carboxylic esters releasing long-chain fatty acids but also on sterol esters, although with different activity and affinity. The differences in the catalytic properties among the proteins of this family are explained by small changes in the hydrophobicity of some regions. One of such versatile enzymes is the sterol esterase/lipase from Ophiostoma piceae (OPE) that acts very efficiently on the two types of substrates. Structurally, OPE is characterized by the presence of a lid formed by a α-helix and two 310-helices rich in hydrophobic amino acids. In this study, the ope gene was modified by directed mutagenesis in order to change specific amino acids in the lid region to modify its structure with the aim of increasing its hydrophobicity. Several recombinant forms of OPE were heterologously produced in Pichia pastoris. In silico molecular dynamics simulations have been used to decipher the mechanistic principles behind the improvements in substrate catalysis. The analyses suggested that the enhanced activity towards hydrophobic substrates such as triglycerides could be due to a better stabilization of the substrate in the lid region as a result of an increased hydrophobicity and an improved topology. These results indicate that in silico simulations can be useful for the optimization of the activity of lipases from the C. rugose-like family for different biotechnological applications.